2 Successful intervention to reduce central line-associated bloodstream infection rate in adult intensive care unit at a specialized tertiary care hospital in riyadh, saudi arabia. (25th October 2019) - Albadawi, Ayham Salah; AlBakheet, Yahya; Yassine, Kassem Abou; AlGhamdi, Eman; Caswell, Angela; Marhoun, Saja; El-Saed, Aiman; Alshamrani, Majid; Balkhy, Hanan
Abstract : Background: Central line-associated bloodstream infection (CLABSI) surveillance in the adult intensive care unit (ICU) in King Abdullah Specialized Children Hospital showed a higher CLABSI rate during the first quarter of 2018. CLABSI is associated with a significant increase in morbidity, mortality, length of hospitalization, and the cost of healthcare. The aim of the current study was to evaluate the impact of a multifaceted improvement project aiming to reduce the rate of CLABSI. Methods: This was an interventional surveillance study. A Plan, Do, Check, Act (PDCA) quality improvement approach was used. The intervention was initiated in March 2018. It focused on the following aspects: standardizing the central line (CL) maintenance practices, creating a designated cart for CL insertion and maintenance, increasing compliance with aseptic techniques and CL insertion and maintenance bundles, educating the healthcare workers and patients on CLABSI prevention, environmental cleaning and disinfections, and instantaneous feedback to the stakeholders about CLABSI events. The intervention engaged multiple partners including infection control, nurses, and physicians. Surveillance methods and CLABSI definition was done according the US National Healthcare Safety Network. Results: During 2018, a total of ten CLABSI events were detected during 2919 central-line days. They included four, four, two, and no events in the first, second, third, and fourth quarters, respectively. After intervention, the rate significantly decreased from 5.2 per 1000 central line-days during the second quarter of 2018, to 3.9 during the third quarter of 2018, and zero during the fourth quarter of 2018 (Mantel-Haenszel chi-square p value of 0.034). Conclusion: A multidisciplinary multifaceted improvement project using quality improvement tools to enforce the evidence-based preventive practices has been successful in reducing the CLABSI rate. The implementation of the improvement project needs to be continued to maintain zero or low CLABSI rates.